EFEKTIVITAS KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA KERJA DALAM MENINGKATKAN KINERJA GURU - Uwat (MADINASIKA, 2021)
The research was motivated by the low performance of teachers, allegedly due to ineffective leadership and an inconsistent work culture. The research aims to analyze and determine: a) the effectiveness of the principal's leadership; b). teacher work culture; c) teacher performance. The research uses an approach with the main data collection tool using an in-depth discussion. Informants were determined purposively, the data obtained were processed and analyzed through data reduction, data presentation, and drawing conclusions. Data validity was tested through technical triangulation. The results of the study show: a) Principal leadership is effective in improving teacher performance. b) Teacher work culture strengthens teacher values ​​and work abilities; c) Leadership and work culture can improve teacher performance. In conclusion, the effectiveness of principals' leadership and work culture can improve teacher performance.